Production Planning and Control Model to Increase On-Time Deliveries Through Demand-Driven MRP and PDCA in a Make-to-Order Environment of Non-primary Manufacturing Industry - Franco-Quispe, Daeli (2021)
El texto completo de este trabajo no está disponible en el Repositorio Académico UPC por restricciones de la casa editorial donde ha sido publicado.